BAHASA SLANG INGGRIS DARI YOUTUBE: STUDI DESKRIPTIF TENTANG BAHASA LISAN GENERASI ALPHA - M. Renaldy Aditya Pratama; Vebrianti Umar; Armin Fani (Yayasan Pendidikan Literasi Borneo, 2026)
The development of digital media, especially YouTube, influences the communication patterns of Generation Alpha in using informal English slang. Students who frequently watch English-language content such as gaming, challenge videos, reaction videos, and entertainment tend to imitate the vocabulary used by content creators in their daily conversations. This study aims to describe the use of English slang obtained from YouTube in the spoken language of Generation Alpha students at SMP Sabilal Muhtadin Banjarmasin. This study employed a descriptive qualitative approach involving three seventh-grade students who actively watch YouTube and use slang in everyday communication. The data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman model consisting of data reduction, data display, conclusion drawing, and verification. The findings showed that the students used various English slang expressions such as bruh, sus, lit, no cap, ez, and chill in informal conversations with peers, especially during gaming activities and social media communication. The slang expressions were acquired through repeated exposure to YouTube content watched by the students every day. In addition, the use of slang was more dominant in informal situations than in formal interactions at school. This study indicates that YouTube has become one of the influential media affecting the use of English slang in the spoken language of Generation Alpha